Prognostic value of the systemic inflammation modified Glasgow prognostic score in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy: Results from a large multicenter international collaboration - Soria, Francesco; Giordano, Andrea; D'Andrea, David; Moschini, Marco; Rouprêt, Morgan; Margulis, Vitaly; Karakiewicz, Pierre I; Briganti, Alberto; Bensalah, Karim; Mathieu, Romain; Chlosta, Piotr; Babjuk, Marek; et al. (Urologic oncology, 2020)
INTRODUCTION AND OBJECTIVES: To evaluate the prognostic role of modified Glasgow prognostic score (mGPS) for the prediction of oncological outcomes in a retrospective large multicenter cohort of upper tract urothelial carcinoma (UTUC) patients treated with radical nephroureterectomy (RNU). MATERIALS AND METHODS: We retrospectively analyzed a multicenter cohort of patients treated with RNU for clinically nonmetastatic UTUC. Multivariable logistic regression analyses were performed to evaluate the ability of mGPS to predict nonorgan confined (NOC) disease and lymph-node involvement (LNI) at RNU. Multivariable Cox-regression models were performed to evaluate the preoperative and postoperative prognostic effect of mGPS on survival outcomes. RESULTS: Overall, 2,492 patients were included in the study. Of these, 1,929 (77%), 530 (21%), and 33 (1%) had a mGPS of 0, 1, and 2, respectively. mGPS was associated with characteristics of tumor aggressiveness and independently predicted LNI and NOC at RNU (both P < 0.05). On univariable and multivariable Cox-regression analyses, higher mGPS was independently associated with recurrence-free, cancer-specific, and overall survival, both in a preoperative and in a postoperative setting. The inclusion of mGPS significantly improved the discrimination of a preoperative model for the prediction of oncologic outcomes compared to standard prognosticators. CONCLUSIONS: We found that mGPS is independently associated with clinicopathologic features and survival outcomes after RNU. Future studies should investigate the role of mGPS in a panel of preoperative markers for the prediction of NOC and LNI in UTUC patients, thus possibly improving the selection for perioperative systemic therapy.
Keywords: senioři; UTUC; Inflammation; mezinárodní spolupráce; Retrospective Studies; Prognosis; lidé; Upper tract urothelial carcinoma; nádory močovodu; karcinom z přechodných buněk; zánět; Middle Aged; International Cooperation; mužské pohlaví; míra přežití; Nephroureterectomy; Kidney Neoplasms; Ureteral Neoplasms; Prediction; ženské pohlaví; prognóza; retrospektivní studie; Humans; Glasgow prognostic score; Survival Rate; nefroureterektomie; lidé středního věku; Carcinoma, Transitional Cell; Female; Aged; nádory ledvin; Male